Experimental and numerical investigation of the correlation between radiative and convective heat-transfer coefficients at the cooled wall of a real-sized room - Acikgoz, Ozgen; Kincay, Olcay (ELSEVIER SCIENCE SA, 2015)
Radiant heating and cooling systems can be utilized in association with renewable energy sources and are currently being used in newly constructed homes, as well as in buildings where heating and cooling systems have been converted from conventional systems to these systems. Thus, for a radiant system, the fundamental characteristic parameters, such as radiative, convective and total heat-transfer coefficients, carry the utmost importance. In the present study, these coefficients were determined through measurements from a test facility as well as numerical case studies. This article provides the heat-transfer coefficients from experimental research on cooled hydronic radiant panels placed on a chamber's walls. The experimental study utilized 4 different flow rates between 0.08 kg/s and 0.15 kg/s, and water supply temperatures between 14 degrees C and 19 degrees C. Furthermore, computational and theoretical case studies found that the ratio of radiative to convective heat transfer coefficients (h(r)/h(c)) varied in the range of (0.88-1.79), throughout all of the experimental and numerical case study results. Also, correlations for the proportions of the coefficients and the radiative heat-transfer coefficient were derived. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heat-transfer coefficients; Radiant wall cooling; Hydronic radiant cooling; Enclosures; Radiation; Convection; Heat transfer; NATURAL-CONVECTION; THERMAL COMFORT; COOLING SYSTEMS; RADIANT; SURFACES; PANEL; FLOOR; CAPACITY; Construction & Building Technology; Energy & Fuels; Engineering